Efektifitas Penggunaan Media Video Animasi terhadap Pengetahuan Pencegahan Pelcehan Seksual pada Anak Usia Dini di TK Aisyiyah Kota Bukittinggi - Kartika Mariyona; Pagdya Haninda Nusantri Rusdi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
There are more and more cases of sexual harassment crimes in Indonesia, not only among teenagers but also young children who are the targets of sexual crimes. What happened made the government issue a law as a preventive measure to reduce the level of sexual violence against children, namely Law No. 35 of 2014 concerning Child Protection with the aim of "Effectiveness of Using Animated Video Media on Knowledge of Prevention of Sexual Harassment in Early Childhood in Aisyiyah Kindergarten" . The introduction of sex knowledge education in early childhood must of course be conveyed in an attractive and effective media. This research is a descriptive research with a qualitative approach. Qualitative descriptive method is a research method based on the philosophy of postpositivism used to examine the condition of natural objects (as opposed to experiments) where the researcher is the key instrument. The data collection technique was done by triangulation (combined). This type of research is case studies, which are qualitative studies in which researchers conduct in-depth exploration of programs, events, processes, activities, against one or more people. The results of this study where according to Informant I and Informant II animated videos are very effective in providing information to increase knowledge to early childhood about sexual harassment.